Biodiversity conservation: history, protected areas and hotspots - Huntley, B.J. (2019)
Angola is a large country of great physiographic, climatic and habitat diversity, with a corresponding richness in animal and plant species. Legally protected areas (National Parks and Game Reserves) were established from the 1930s and occupied 6% of the country’s terrestrial area at the time of independence in 1975. As a consequence of an extended war, the Protected Areas were exposed to serious neglect, poaching and land invasions. Many habitats of biogeographic importance, and many rare and endemic species came under threat. The recently strengthened administration gives cause for optimism that a new era for biodiversity conservation is at hand. The Protected Areas system was greatly expanded in 2011, and increasing resources are being made available towards achieving management effectiveness